Pengembangan Bahan Ajar Menulis Teks Negosiasi Berbasis Pengalaman pada Siswa Kelas X SMK Swasta As Syifah Kisaran - Rusda (Medan Resource Center, 2022)
This study aims to develop teaching materials for writing experience-based negotiation texts for class X students 0f Kisaran Private Vocational School (SMK). This research is a research on the development of the Borg and Gall model (2003). The stages carried out include preliminary studies, drafting, expert and user assessments, and field tests. Assessments from experts and users indicate that the teaching materials for writing negotiation texts meet the eligibility criteria. The feasibility assessment focused on four components, namely content, language, presentation, and graphics with an average percentage of 88.5%. Effectiveness is based on the value of the results of field trials with reference to the minimum completeness criteria (KKM) for writing negotiation texts, which is 70. The value of the results of field trials reaches an average of 82.77 with classical school completeness. The achievement of the student's average score which is higher than the KKM value indicates that the teaching materials developed are effective so that they are suitable for use in the learning process of writing negotiation texts. Keywords: Development; teaching materials; writing; negotiation text; experience-based